Exponential integration of the linear assignment flow - Zeilmann, Alexander; Savarino, Fabrizio; Petra, Stefania; Schnörr, Christoph (Proceedings in applied mathematics and mechanics, 2019)
We introduce the linear assignment flow as an approximation of the full nonlinear assignment flow, which is a method for contextual data labeling on arbitrary graphs. The linear assignment flow is a dynamical system evolving on the tangent space of a statistical manifold.
Gesehen am 18.01.2021